European interests in the Global South: capabilities of comprehensive forecasting - Anna K. Ivanova; Denis P. Eremin (Научно-аналитический вестник Института Европы РАН)
The escalating interest of European countries in Africa and the Middle East in recent years has emerged as a significant response to overarching global geopolitical transformations. These shifts have compelled both the United Kingdom and countries of the European Union to critically reassess their political and economic strategies within the contexts of the Global South. The global academic community is actively engaged in dissecting the multifaceted activities governing the interactions between European stakeholders and their counterparts in Africa and the Middle East. Both foreign and Russian scholars are particularly focused on the concept of raw materials sovereignty within the EU framework. As international economic and technological competition intensifies, there is an urgent imperative to innovate analytical framework that can enhance predictive capabilities concerning the implications of actions taken by state entities, non-governmental organizations, multinational corporations, and other interest groups operating in these regions. This article proposes the utilization of three key parameters – Interests, Sources, and Activities (ISA) – as determinants for evaluating the significance of research domains. By applying the ISA framework, the authors elucidate emerging trends and focal areas pertaining to the activities of these actors, thereby highlighting aspects that necessitate heightened scrutiny in regional analysis.